Analysis of the Environment Impact on the Inclusion of Children with Special Educational Needs - TURLUBEKOVA, Marzhan; BIRYUKOV, Valeriy; MAGRUPOVA, Zulfiya; KISHIBEKOVA, Galiya; BUGUBAYEVA, Roza (Journal of Environmental Management and Tourism; Vol 14 No 5 (2023): JEMT, Volume XIV, Issue 5(69), Fall 2023DO - 10.14505/jemt.v14.5(69).17, 2023)
This paper highlights the critical role of the environment in facilitating the inclusion of children with special education needs (SEN) in educational settings. The physical environment, social interactions, curriculum, instructional practices, and policy frameworks all contribute to creating an inclusive environment. Considering and addressing the impact of these environmental factors, educators, policymakers, and school leaders can promote the successful inclusion and participation of children with SEN, ultimately enhancing their educational experiences and outcomes. Further research is needed to delve deeper into specific environmental factors and their interrelationships to develop comprehensive strategies for promoting inclusive education.